Executives Under Pressure. - Marshall, Judi. and Cooper, Cary L. (New York Praeger Publishers, Praeger Special Studies, 1979)
In Executives under Pressure Judi Marshall and Cary Cooper show that stress emerges from the fit between the person and the environment and not simply from job pressure. So some executives, in particular engineering managers, achieve very great satisfaction from job challenges.
Keywords: Economics